Unveiling the influence mechanism of La alloy on the oxidation behavior of Cu contact materials: A combined experimental and density functional investigation - Bingtian Li; Zhenjie Guan; AnRan Li; Ziyao Chen; Weijian Li; Liang Zhen; Wenzhu Shao (Journal of Materials Research and Technology)
The preferential oxidation of alloying elements has long been recognized as the primary mechanism underlying the oxidation resistance of copper alloys. However, the presence of various alloy phases within the Cu matrix complicates the oxidation behavior. Herein, combined DFT calculations and antioxidation experiment were conducted to evaluate the oxidation behavior and underlying mechanism of Cu–La alloys. The results indicate that the oxidation resistance of Cu is significantly enhanced by La element with a reduced mass gain of 49% at 100 °C for 100 h. The effects of oxidation behavior of Cu6La on the oxidation resistance of Cu is further explored by DFT calculations. It reveals that the Cu6La phase with a low work function exhibits a strong affinity for the O atoms. However, the diffusion activation energy of the absorbed O is calculated to be lower in Cu6La than that of O in Cu, which is conducive to mitigate the further erosion of O on Cu matrix. Moreover, the Cu2O–La layer formed on the Cu6La surface is more stable and the oxygen diffusion coefficient in it is lower, which impedes the entry of oxygen. This work advances the understanding of alloying effect on oxidation of Cu surfaces that can be extended to other metal surfaces.